Attitude of Union Members Toward Their Union (Relations industrielles / Industrial Relations, 1952)
The article briefly reviews "Attitude of Union Members Toward Their Union," by Herbert G. Heneman, Jr., and Dale Yoder; published by the Industrial Relations Center, University of Minnesota, Minneapolis 14, Minn. Reprinted from Labor and Nation, Summer 1951 issue (4 pages).

Contrôle de la main-d'oeuvre dans les métiers du bâtiment de la région des Cantons de l'Est: rapport (Relations industrielles / Industrial Relations, 1952)
The article reviews "Contrôle de la main-d'oeuvre dans les métiers du bâtiment de la région des Cantons de l'Est: rapport," prepared by Charles E. Thérien, statistician, Service de l'Aide à l'Apprentissage, décembre 1951 (28 pages).

Eight[h] Laval Industrial Relations Convention: Human Problems in Production (Relations industrielles / Industrial Relations, 1952)

Factors in Successful Collective Bargaining: Report of the Subcommittee on Labor and Labor-Management Relations, 82nd Congress, 1st Session (Relations industrielles / Industrial Relations, 1952)
The article reviews "Factors in Successful Collective Bargaining: Report" of the Subcommittee on Labor and Labor-Management Relations, 82nd Congress, 1st Session, (57 pages).

Huitième Congrès des relations industrielles de Laval : problèmes humains du travail (Relations industrielles / Industrial Relations, 1952)
An article from Relations industrielles / Industrial Relations, on Érudit.

Index du volume 7 - 1951-52 (Relations industrielles / Industrial Relations, 1952)

La mesure de la productivité (Relations industrielles / Industrial Relations, 1952)
The article reviews "La mesure de la productivité," by Jean Dayre, conseiller technique du Comité national de la productivité. Series of three articles published successively in the october, november and december 1951 issues of the journal, Travail et Méthodes. Editions Science et Industrie, Paris.

Labor Views Collective Bargaining (Relations industrielles / Industrial Relations, 1952)
The article reviews "Labor Views Collective Bargaining," by J.A. Beirne, President, Communications Workers of America (CIO), 1952 (22 pages).

Le patronat devant le syndicalisme (Relations industrielles / Industrial Relations, 1952)
The article reviews "Le patronat devant le syndicalisme," summayr of the 12th congress of the Fédération des Patrons catholiques de Belgique, held on 15-16 December 1951, published in the Bulletin social des Industriels, January 1952.

Livres reçus [v. 8, no. 1 (1952)] (Relations industrielles / Industrial Relations, 1952)

Périodiques (Relations industrielles / Industrial Relations, 1952)
List of journals that are pertinent to the field.

Problèmes du travail féminin (Relations industrielles / Industrial Relations, 1952)
The article reviews the book, "Problèmes du travail féminin," by Roger Chartier, proposed for the teaching of labour relations, Centre de culture populaire de Laval, Université Laval, 1952 (61 pages).

Publications récentes / Recent publications [v. 7, no. 3 (1952)] (Relations industrielles / Industrial Relations, 1952)

Publications récentes [v. 7, no. 4 (1952)] (Relations industrielles / Industrial Relations, 1952)

Publications récentes [v. 8, no. 1 (1952)] (Relations industrielles / Industrial Relations, 1952)
Bibliography with subject headings.

Semaine sociale des catholiques italiens (Relations industrielles / Industrial Relations, 1952)

Should Conciliation Boards be Abolished? (Relations industrielles / Industrial Relations, 1952)
Should Conciliation Boards be abolished? This is an interesting question raised up in the contributed editorial of the 1952 winter issue of "Public affairs" and presented in the following way.

Strikes (Relations industrielles / Industrial Relations, 1952)
The article reviews the booklet, "Strikes," by William Goldner, edited by Irving Bernstein, Institute of Industrial Relations, University of California, Berkeley, 1951 (50 pages).

Tribute to Laval University Centenary at the Industrial Relations Convention. (Relations industrielles / Industrial Relations, 1952)

L'adulte des milieux ouvriers, v. I: Essai de psychologie sociale, v. II: Essai de psychologie pastorale - Bélanger, Gilles-M. (Relations industrielles / Industrial Relations, 1952)
The article reviews the books, "L'adulte des milieux ouvriers," v. I: Essai de psychologie sociale (586 pages), v. II: Essai de psychologie pastorale (402 pages) by Simon Ligier.

Conséquences juridiques des décisions de la Conférence internationale du Travail - Binet, Henri (Relations industrielles / Industrial Relations, 1952)
L'auteur décrit la composition de la Conférence internationale du Travail, « assemblée annuelle des Etats membres de l'Organisation internationale du Travail ». L'O.I.T. se propose comme but l'extension de la « justice sociale, dans l'intérêt de la paix mondiale ». Après une brève analyse des moyens dont dispose cet organisme, l'auteur établit les nécessaires distinctions entre trois types de décisions sur lesquelles l'O.I.T. peut s'arrêter: résolutions, recommandations et conventions. Il souligne ensuite le caractère de l'obligation des Etats-membres en face des conventions, parlant du rôle de l'opinion publique et du mécanisme des commissions d'enquête. L'auteur s'arrête assez longuement sur le cas des Etats fédératifs, ainsi le Canada, qui jouissent d'une situation privilégiée, car ici la compétence législative en matière du travail n'est pas réservée entièrement au pouvoir central. A la fin de l'article sont étudiées les contestations possibles et énumérées les sanctions éventuelles.

Juridical Consequences of the Decisions of the International Labour Conference - Binet, Henri (Relations industrielles / Industrial Relations, 1952)
The Author describes the International Labour Conference, as the "annual meeting of the Member States of the International Labour Office. " The I.L.O. has as purpose "to promote social justice in the interest of world peace.'' After a short analysis of the means at the disposal of this organization, the Author establishes the necessary distinctions between three types of decisions which the I.L.O. may reach: Resolutions, Recommendations and Conventions. He then emphasizes the characteristics of the obligation of the Member States towards conventions, discussing the rôle of public opinion and of the functions of boards of inquiry. The author gives considerable attention to the case of federated states such as Canada, who enjoy a privileged situation, as the legislative jurisdiction here on labour questions is not entirely confined to the central authority. The possible points of dispute are studied in conclusion as well as the eventual sanctions.

Employers' Associations and Collective Bargaining in New York City - Chartier, Roger (Relations industrielles / Industrial Relations, 1952)
The article reviews the book, "Employers' Associations and Collective Bargaining in New York City," by Jesse Thomas Carpenter.

L'évaluation du mérite personnel - Chartier, Roger; Fuerstenthal, A. H. (Relations industrielles / Industrial Relations, 1952)
Etude à la fois théorique et pratique des nombreux problèmes que pose l'application d'un plan d'Evaluation du mérite personnel dans les entreprises. Les auteurs définissent d'abord cette technique relativement récente, en indiquent les buts, les responsables et les sujets, suggèrent une fréquence optima pour les séances d'évaluation et énumèrent les conditions et les caractéristiques de formules pratiques d'évaluation. Ils décrivent ensuite les diverses étapes d'une méthode qu'ils ont élaborée à la suite d'une expérience d'un an avec des centaines d'employés de bureau d'une compagnie canadienne à l'étranger.

Merit Rating - Chartier, Roger; Fuerstenthal, A. H. (Relations industrielles / Industrial Relations, 1952)
The authors are using both the theoretical and the practical approach in their discussion of various aspects of Merit Rating. After stating what Merit Rating is, why, when and on what it is used, how it works, and by whom and on whom it is applied, the Authors describe at length, and with illustrations, the different steps of a new method of service appraisal which they have devised on the basis of a one-year experience with hundreds of clerical workers in a big Canadian public utility concern abroad.

Revised Profit Sharing Manual - Dion, Gérard (Relations industrielles / Industrial Relations, 1952)
The article reviews the book, "Revised Profit Sharing Manual," issued by the Council of Profit Sharing Industries.

L'efficacité sociale du système économique - Dubé, Yves (Relations industrielles / Industrial Relations, 1952)
The article reviews the book, "L'efficacité sociale du système économique," by R. Dehem, Institut de recherches économiques et sociales, Place Monseigneur Ladeuze, Louvain.

[Arbitration awards, November 1951-February 1952] - Gagné, Jean-H. (Relations industrielles / Industrial Relations, 1952)
The awards studied under this heading were rendered during the months of November and December of last year and January and February of this year. An outline of the points which we found to be of the most interest in these awards follows, under the various subjects covered.

[Les sentences arbitrales, juillet-novembre 1952.] - Gagné, Jean-H. (Relations industrielles / Industrial Relations, 1952)
Les sentences arbitrales étudiées dans le présent numéro sont celles rendues durant les mois de juillet, août, septembre, octobre et novembre 1952. Nous ne rapportons que les sentences contenant des commentaires qui peuvent être d'intérêt particulier pour nos lecteurs.

[Les sentences arbitrales, mars-juin 1952] - Gagné, Jean-H. (Relations industrielles / Industrial Relations, 1952)
Les sentences étudiées dans la présente chronique ont été rendues pendant les mois de mars, avril, mai et juin de cette année. Suit un exposé des points qui nous ont le plus frappés dans leur contenu, sous les différents sujets mentionnés.

"Progress-Sharing" can mean Industrial Peace - Gagné, Jean-H. (Relations industrielles / Industrial Relations, 1952)
The article briefly reviews "'Progress-Sharing' can mean Industrial Peace," published in Reader's Digest, September, 1952, Canadian Edition, pages 81 to 85.

Droit et économie politique - Gaudreau, Claude (Relations industrielles / Industrial Relations, 1952)
Cet article est un bref exposé de quelques opinions respectives de Gaëtan Pirou, économiste, et de Georges Ripert, juriste, sur le droit et l'économie politique et une prise de position personnelle de l'auteur sur le sujet. L'économie politique est-elle une discipline humaine, une science, une doctrine ? N'existe-t-il pas entre les deux des rapports et des contacts, qu'il soit utile et peut-être même nécessaire aux deux genres de spécialistes de connaître ? L'auteur précise certaines distinctions intéressantes à retenir entre fait économique et fait juridique, loi scientifique et loi positive, science morale et science expérimentale. Il termine en soulignant que le droit, l'économique et les autres disciplines sociales se complètent avantageusement avec toutes les conséquences qui en découlent.

Law and Political Economy - Gaudreau, Claude (Relations industrielles / Industrial Relations, 1952)
This article is a summary of the respective opinions of Gaëtan Pirou, economist and of Georges Ripert, jurist, on Law and Political Economy, and the author's personal position on the subject. Is Political Economy a human discipline, a science, a doctrine? Does there not exist between the two, relationships and contacts that would be useful and perhaps even necessary to the two kinds of specialists to understand? The author points out certain interesting distinctions to be noted between economic fact and juridical fact, scientific law and positive law, moral science and experimental science. He concludes in emphasizing that the law, economics and other social disciplines complete one another to advantage with all the consequences arising from this.

Rôle du secrétaire de comité paritaire - Gérin, Raymond (Relations industrielles / Industrial Relations, 1952)
Dans cet article, l'auteur veut montrer le rôle capital que le secrétaire de comité paritaire, de par ses fonctions, doit jouer. Ces fonctions varient d'un comité paritaire à l'autre; mais dans l'ensemble, ce sont celles déterminées par la loi de la Convention collective et suggérées par les règlements-types recommandés par le ministère du Travail. Au-delà de ces fonctions, le secrétaire a un rôle à exercer dans la marche et l'orientation du comité paritaire, en tant qu'administrateur, en tant que spécialisé dans un secteur des relations du travail et possédant un sens social averti. Pour agir avec efficacité et durabilité, il doit possérer un ensemble particulièrement riche de qualités et de ressources et pouvoir assurer ainsi la continuité et l'orientation de cet organisme dont il est mandaté.

The Role of the Secretary of a Parity Committee - Gérin, Raymond (Relations industrielles / Industrial Relations, 1952)
In this article, the author wishes to show the important role that the secretary of a parity committee, by his functions, must play. These functions vary from one parity committee to another, but generally are those determined by the Collective Agreement Act and suggested by the sample regulations recommended by the Department of Labour. In addition to these duties, the secretary takes part in the conduct and orientation of the parity committee, not only as administrator but also as a specialist in a sector of labour relations possessing an awakened social conscience. In order to act with efficiency and durability, he must be particularly rich in qualities and resources and thus be able to assure the continuation and orientation of this organization with which he is entrusted.

Démocratie ouvrière en 1952 - Gosselin, Emile (Relations industrielles / Industrial Relations, 1952)
Dans une première section, l'auteur fait un bref commentaire sur la nature et l'importance des congrès annuels des mouvements ouvriers canadiens et sur l'action politique de ces derniers. Le lecteur trouvera dans la deuxième partie du travail un compte-rendu des discours, rapports et résolutions présentés lors de ces réunions.

Évaluation des facteurs techniques et humains dans la direction - Gosselin, Emile (Relations industrielles / Industrial Relations, 1952)
Le travailleur n'est pas une partie de la machine industrielle, un outil dont la valeur est uniquement mesurée par les dollars de production; c'est pour cette raison qu'il ne peut répondre mathématiquement aux stimulants imposés par la gérance seule. Il doit pouvoir se sentir considéré comme un homme, un être humain et non seulement comme un instrument à la production. Il aime à être consulté et apprécie qu'on tienne compte de son opinion; il veut se sentir intégré à l'entreprise. Dans une telle atmosphère de collaboration, les relations patronales-ouvrières seront meilleures et les difficultés au sein de l'entreprise seront amoindries comme l'auteur le démontre par un exemple qu'il présente au lecteur. Il expose brièvement quelques principes susceptibles d'améliorer les relations entre la direction et ses employés. Il indique les fonctions de l'entreprise, le rôle de l'autorité et les conditions de son exercice. La direction ne peut être efficace que si elle tient compte des aspirations du travailleur et du syndicat.

Labour Democracy in 1952 - Gosselin, Emile (Relations industrielles / Industrial Relations, 1952)
In the first section, the author comments briefly on the nature and the importance of the annual conventions of the Canadian labour bodies and on their political action. The reader will find in the second section a summary of the speeches, reports and resolutions presented during these conventions.

Films for Use in Canadian Industry - Hill, Rowland (Relations industrielles / Industrial Relations, 1952)
In this article, the author emphasizes that moving-pictures, formerly identified with entertainment and more recently as an aid to education, have been used by industry, but that there still remains much to do to cover the field of usefulness of the film itself. Movies had an active part during the war and should continue this function during peace. The Federal Department of Labour is attempting to promote a wider use of movies concerned with the field of labour and is doing this by means of a catalogue and films supplement, of filmstrips and of library. The author, moreover, suggests the different possible sources for obtaining available films.

L'indice des prix à la consommation - Hodgson, James (Relations industrielles / Industrial Relations, 1952)
Brève étude du nouvel indice appelé Indice des prix à la consommation (l.P.C.) qui remplacera l'Indice du coût de la vie (I.C.V.). Pour en arriver à un tel changement, on fit appel à des spécialistes qui y travaillèrent pendant près de trois ans. Au cours de l'enquête commencée en 1948, les méthodes les plus modernes d'échantillonnage furent utilisées. Au lieu de 1935-1939 la période de base fut fixée à 1949. Etant donné l'importance croissante de l'indice dans le monde du travail, l'auteur analyse de façon sommaire les modifications apportées à l'ancien indice et souligne les problèmes connexes amenés par un tel changement.

The Consumer Price Index - Hodgson, James (Relations industrielles / Industrial Relations, 1952)
A brief study of the new index called Consumer Price Index (C .P. I.) which will replace the Cost of Living Index (C. L. I.). In order to make such a change, specialists were called in to work on this for nearly three years. During the survey begun in 1948, the most modern methods of sampling were used. Instead of 1935-1939, the base period chosen was 1949. In view of the increasing importance of the index in the labour world, the author analyses briefly the changes made in the former index and emphasizes the problems involved in such a changeover.

L'éducation ouvrière aux États-Unis - Jolicoeur, Fernand (Relations industrielles / Industrial Relations, 1952)
Aperçu général de l'éducation ouvrière aux Etats-Unis dont l'évolution a suivi celle du syndicalisme américain. Cette étude donne une idée de la conception que les unions américaines se font de l'éducation ouvrière et des moyens qu'elles emploient pour la poursuivre. L'auteur affirme qu'elles attachent beaucoup d'importance à la formation syndicale de leurs membres, mais ne vont pas plus loin sauf rares exceptions. Elles ont développé cependant, des techniques d'éducation des adultes qui pourraient servir efficacement à une formation beaucoup plus vaste.

The Education of Labour in the United States - Jolicoeur, Fernand (Relations industrielles / Industrial Relations, 1952)
In a general picture of the education of labour in the United States of which the evolution has followed that of American unionism, this study gives an idea of the conception that the American unions have of the education of labour and the methods they use to carry it out. The Author asserts that they attach much importance to the training of their members in union questions, but do not go any further except in particular cases. They have developed, however, techniques in adult education which could serve efficiently for a much wider formation.

Un Collège ouvrier - Jolicoeur, Fernand (Relations industrielles / Industrial Relations, 1952)
La C.T.C.C. inaugurera à Québec, en novembre prochain, un Collège ouvrier dont les cours dureront quatre semaines....

Le concept canadien de sécurité sociale - Martin, Paul (Relations industrielles / Industrial Relations, 1952)
L'auteur, au lieu de s'arrêter à la cristallisation, sous forme de lois, du concept de sécurité sociale, analyse le cadre actuel des mesures sociales administrées sur le plan local, fédéral et provincial; il étudie les principes sur lesquels les programmes reposent et auxquels ils doivent se conformer. Pour établir de tels programmes, il faut tenir compte des facteurs historiques, des profondes convictions religieuses, de l'expérience des sociétés anciennes et des particularités géographiques et culturelles. A l'Etat incombe la responsabilité d'aider les individus à mieux pourvoir à leur sécurité et à leur bien-être; l'Etat ne doit pas être omnipotent et détruire toute initiative privée ou collective créée dans ce sens. A chacun de leurs échelons, les administrations publiques canadiennes contribuent, d'une façon vitale, au bien-être social.

Occupational Corporative Order - Pope Pius XII (Relations industrielles / Industrial Relations, 1952)
The following text is an English translation by the National Catholic Welfare Conference of the address pronounced in January 31th 1952 by His Holiness Pope Pius XII to the Italian Catholic Association of Employers in which he asked for the Christian spirit as the basis for the social order and criticized forced co-determination.

Social Documents: Credit - Pope Pius XII (Relations industrielles / Industrial Relations, 1952)
The following text is an English translation by the National Catholic Welfare Conference of the discourse given in the French language by His Holiness Pope Pius XII on October 24, 1951, to delegates from 46 nations attending the International Congress on Credit Questions. In his discourse, the Pontiff discussed the moral and social importance of credit and encouraged its fruitful extension.

Période tragique dans l'histoire du Rhode-Island - Quirk, Charles (Relations industrielles / Industrial Relations, 1952)
Cet article n'est qu'un court extrait d'une intéressante étude sur les problèmes de l'emploi au Rhode-Island de 1935-1950; il a pour but de faire connaître au lecteur l'évolution historique et économique de l'industrie du textile au Rhode-Island. L'auteur décrit la concurrence qui s'établit entre le Nord et le Sud; au début, minime, elle s'accrut dans la suite pour prendre des proportions désastreuses et amener ses conséquences funestes: diminution de la productivité, migration des moulins vers le Sud et chômage général. L'histoire du textile de la Nouvelle-Angleterre fournit l'exemple d'un système conforme au « laissez-faire » du capitalisme libéral: recherche du plus grand profit possible sans souci de responsabilité sociale. Ce système doit être soumis à la morale des affaires ou se détruire lui-même.

La coopération dans l'histoire économique moderne - Raftis, J. A. (Relations industrielles / Industrial Relations, 1952)
L'auteur, dans cet article a voulu dégager de façon très sommaire, le fonctionnement particulier des institutions coopératives dans la vie économique moderne. Après un court résumé historique pour démontrer les multiples efforts tentés pour organiser l'économie sur la base de propriété commune de production, il critique les principes énoncés par le mouvement coopératif et examine ensuite la structure réelle de cet organisme. Son attention se porte sur les problèmes posés, par la mise en application des principes coopératifs au sein de l'économie moderne. Il conclut en suggérant qu'un programme d'éducation ayant pour but de rendre les individus conscients de leur potentiel industriel peut être la seule solution et amènerait d'heureux résultats.

Apprenticeship Assistance - Thérien, Charles (Relations industrielles / Industrial Relations, 1952)
This article on the Act to assist apprenticeship and the enhancing of human capital has as its aim to remind the reader of some important ideas concerning this Act and its application in the Province of Quebec. The author recalls the principle at the basis of the Act, then emphasizes the moral and social aspect, examines its realizations within the profession itself, and views its future among the problems which it must meet. He concludes by insisting on the necessity of a very close cooperation between the various organizations trusted with the training of youth to form specialized labour.

Aide à l'apprentissage - Thérien, Charles-E. (Relations industrielles / Industrial Relations, 1952)
L'exposé de cet article sur la Loi de l'aide à l'apprentissage et de la mise en valeur du capital humain a pour but de rappeler au lecteur certaines notions importantes concernant cette loi et sa mise en application dans la Province de Québec. L'auteur évoque le principe à la base de la loi, en souligne ensuite l'aspect moral et social, examine ses réalisations au sein de la profession et envisage son avenir à travers les problèmes auxquels elle doit faire face. Il termine en insistant sur la nécessité d'une collaboration très étroite entre les divers organismes chargés de l'entraînement des jeunes pour former une main-d'oeuvre spécialisée.

Hours of Work - Tousignant, Fabienne (Relations industrielles / Industrial Relations, 1952)
The article reviews "Hours of Work," by William Goldner, edited by Irvin Bernstein, published by the Institute of Industrial Relations, University of California, Berkeley, 1952 (63 pages).

Méthodes et techniques des relations humaines - Tousignant, Fabienne (Relations industrielles / Industrial Relations, 1952)
The article briefly reviews "Méthodes et techniques des relations humaines," by Guy-G. Essculier, report presented on 6 July 1952 at the Journée d'Etudes du Comité pour l'Amélioration des Relations Humaines dans l'Economie, published in Travail et Méthodes, septembre 1952 (3 pages). Editions Science et Industrie, Paris.

Sécurité syndicale et conventions collectives de travail - Tousignant, Fabienne (Relations industrielles / Industrial Relations, 1952)
An article from Relations industrielles / Industrial Relations, on Érudit.

Union Security and Collective Labour Agreements - Tousignant, Fabienne (Relations industrielles / Industrial Relations, 1952)

Le cinéma dans les usines - Vanasse, Jean-Paul (Relations industrielles / Industrial Relations, 1952)
Cet article a pour but de renseigner le lecteur sur l'utilisation du cinéma comme moyen de formation pour les milieux du travail. L'auteur, au moyen d'exemples, en souligne le rôle social vis-à-vis les groupes de la société, le rôle d'information et d'éducation vis-à-vis les travailleurs eux-mêmes (renseignements sur l'industrie, les affaires, les organisations ouvrières, les comités mixtes de production, les relations patronales-ouvrières, la sécurité industrielle et sociale, etc...). Les patrons et les ouvriers se convainquant de plus en plus des possibilités du cinéma adoptent à l'endroit des cinéastes une attitude d'étroite coopération. De l'utilisation de ces films accompagnés de discussion ou de causerie, résulte une plus grande collaboration entre employeurs et employés avec toutes les conséquences heureuses qui en découlent.